Associations between Early Markers of Parkinson's Disease and Sarcopenia - Drey, Michael; Hasmann, Sandra E.; Krenovsky, Jan-Peter; Hobert, Markus A.; Straub, Stefanie; Elshehabi, Morad; von Thaler, Anna-Katharina; Fallgatter, Andreas J.; Eschweiler, Gerhard W.; Suenkel, Ulrike; Berg, Daniela; Maetzler, Walter (Frontiers in Aging Neuroscience, 2017)
Introduction: Sarcopenia and Parkinson’s disease (PD) are both common age-related syndromes, and there is preliminary evidence that the probability of the co-occurrence of these syndromes within one individual is higher than expected. However, it is unclear to date whether one of the syndromes induces the other, or whether there may be common underlying causes. This pilot study thus aimed at investigating the association of the features of increased risk for PD with early stage sarcopenia (ESS). Method: Two hundred and fifty-five community-dwelling individuals were recruited from the Tübinger evaluation of Risk factors for Early detection of NeuroDegeneration (TREND) study. The following features that are associated with an increased risk for future PD were evaluated: the motor part of the Unified PD Rating Scale (UPDRS-III), hyperechogenicity of the substantia nigra, prevalence of lifetime depression, hyposmia, REM sleep behaviour disorder and the recently introduced probability score for prodromal PD. Sarcopenia was defined according to the European Working Group on Sarcopenia in Older People, which was adapted to this cohort of healthy adults. Multiple linear regression analysis was used to identify associations of PD-related features with ESS. Results: The UPDRS-III score was significantly associated with ESS. The result remained significant after the adjustment for age, gender and physical activity. No association was found between the other PD-related features and ESS. Conclusion: The significant association of the UPDRS-III score with ESS in this cohort might indicate a common and early pathway in both diseases and supports the existence of an “extended neurodegenerative overlap syndrome”. Moreover, the potential of EES to serve as a prodromal marker of PD should be evaluated in future studies.